2023
DOI: 10.1002/adhm.202203237
|View full text |Cite
|
Sign up to set email alerts
|

Silk‐in‐Silk Nerve Guidance Conduits Enhance Regeneration in a Rat Sciatic Nerve Injury Model

Abstract: Advanced nerve guidance conduits can provide an off‐the‐shelf alternative to autografts for the rehabilitation of segmental peripheral nerve injuries. In this study, the excellent processing ability of silk fibroin and the outstanding cell adhesion quality of spider dragline silk are combined to generate a silk‐in‐silk conduit for nerve repair. Fibroin‐based silk conduits (SC) are characterized, and Schwann cells are seeded on the conduits and spider silk. Rat sciatic nerve (10 mm) defects are treated with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…Semmler et al obtained a silk-in-silk conduit, combining silks from Bombyx mori and spider Trichonephila edulis, which acted as an internal guiding structure. Surprisingly, the double SF scaffolds showed in vivo regenerative performances comparable to those showed by treatment with autografts [219]. This result should further encourage the use of this methodology as a promising therapeutic tool for nerve injury treatment.…”
Section: Neural Tissue Regenerationmentioning
confidence: 63%
“…Semmler et al obtained a silk-in-silk conduit, combining silks from Bombyx mori and spider Trichonephila edulis, which acted as an internal guiding structure. Surprisingly, the double SF scaffolds showed in vivo regenerative performances comparable to those showed by treatment with autografts [219]. This result should further encourage the use of this methodology as a promising therapeutic tool for nerve injury treatment.…”
Section: Neural Tissue Regenerationmentioning
confidence: 63%
“…Spider silk has emerged as a highly promising luminal filling material in the field of tissue engineering, particularly for enhancing the microenvironment within NGCs to facilitate peripheral nerve regeneration. [19,23,24,26] While previous studies have predominantly focused on investigating the use of dragline silk obtained from the species Trichonephila for nervous tissue engineering, less attention has been paid to other spider species' silk. The search for the ideal NGC-filling material, regardless of being native or recombinant, is still in progress.…”
Section: Discussionmentioning
confidence: 99%
“…[16,17] A steadily growing number of in vivo and in vitro studies have already demonstrated the outstanding regenerative potential of dragline silk. [18][19][20][21][22][23][24][25][26][27] Due to this exceptional success, the field of tissue engineering introduced recombinant proteins that are designed based on native dragline spider silk as a template. [28][29][30] However, the majority of the previously deployed silks, whether recombinant or native, resemble dragline silk of the superfamily of orb-weaving spiders, which represents only 25% of all spider species.…”
Section: Introductionmentioning
confidence: 99%